Evaluation of Dalla Bridge Project in Tikrit City According to Lean Construction - et. al., Ghasar Mohammed Abdulrahman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Aiming In this research was to have a clear view about the construction phases of Dalla Bridge, to see whether its implementation phases matched with the lean principles. In the beginning, interviews through a survey forms were carried out with management of the bridge and other professionals. The results of questionnaire were analyzed by using a statistical software (SPSS). Which showed that lean principles have been applied poorly during the bridge construction. Focusing on the most important principle, Eliminate the Wastes which represent the Core for Lean theory. The implementation was only 6% while 93% of the experts put this principle into the important category. Alternative methods are studied to reduce the wastes found. The uses of self-compacted concrete compared with the use of traditionally vibrated concrete, results showed that 55%of the participants totally agreed that this technique will reduce the work time and labour required while 40% partially agreed that work will be reduced and only 5% Not agreed. The use of prefabricated steel also compared with the traditionally steel reinforcement; results showed that 35% of the participants totally agreed with the use of this technique will reduce the steel activities on site while 65%partially agreed that work will be reduce. Also, the effects of formwork types studied, and it showed that 40% totally agreed that it will speed up the works and 60%partially agreed. The researcher found out there is a high level of acceptance from the Dalla team to apply the principles and tools of Lean, and there is a good compatibility with the terms of lean management to be applied in Iraqi construction projects.